Mechanisms Linking Inflammation to Insulin Resistance - Li Chen; Rui Chen; Hua Wang; Fengxia Liang (International Journal of Endocrinology)
Obesity is now widespread around the world. Obesity-associated chronic low-grade inflammation is responsible for the decrease of insulin sensitivity, which makes obesity a major risk factor for insulin resistance and related diseases such as type 2 diabetes mellitus and metabolic syndromes. The state of low-grade inflammation is caused by overnutrition which leads to lipid accumulation in adipocytes. Obesity might increase the expression of some inflammatory cytokines and activate several signaling pathways, both of which are involved in the pathogenesis of insulin resistance by interfering with insulin signaling and action. It has been suggested that specific factors and signaling pathways are often correlated with each other; therefore, both of the fluctuation of cytokines and the status of relevant signaling pathways should be considered during studies analyzing inflammation-related insulin resistance. In this paper, we discuss how these factors and signaling pathways contribute to insulin resistance and the therapeutic promise targeting inflammation in insulin resistance based on the latest experimental studies.